14.9k views
3 votes
K(x) = x - 2
h(x) = x2 +1
(h + k)(2) =

User Jgritty
by
6.9k points

2 Answers

5 votes

Answer:

5

Explanation:

(h + k)(x) = [(x^2 + 1) + (x - 2)]

=[ x^2 + x -1 ]

then for [(h + k)(2)]....substitute x with 2 and then calculate...,

; (2)^2 + 2 - 1

; 4 + 2 - 1

(h + k)(2) = 5

User Mike Moore
by
6.0k points
5 votes

Answer:

5

Explanation:

(h + k)(x) = x - 2 + 2x + 1

(h + k)(x) = 3x - 1

(h + k)(2) = 3(2) - 1

(h + k)(2) = 6 - 1

(h + k)(2) = 5

User Wingzero
by
5.8k points